An Item Response Theory analysis of the SCOFF Questionnaire in a seventh grade population - Gerald J. Bean (International Journal of School Social Work, 2020)
Eating disorders continue to be of concern to school social workers and health and counseling services staff in schools. There is a substantive need for scales that can help to measure both the extent to which eating disorders exist in a school population and to measure risk for specific students. Given that an eating disorder can be chronic and life-altering, early detection of risk is critically important. The aim of this study was to examine the psychometric properties of a popular eating order screening scale—the SCOFF Questionnaire—in a seventh-grade population using Item Response Theory methods. Epidemiological studies have suggested that the onset for some eating disorders is around 12 years old, which roughly corresponds to being in the seventh grade. The data used in this analysis were collected from 3,298 seventh grade students in eighteen Ohio school districts. Results indicate that SCOFF items vary in their statistical relationship with eating disorder risk and, further, operate differently for male and female students. Recommendations for using the SCOFF Questionnaire in school settings are presented.
Keywords: SCOFF Questionnaire; measurement; psychometrics; item response theory; eating disorder risk